Partial amniotic carbon dioxide insufflation (PACI) during minimally invasive fetoscopic interventions on fetuses with spina bifida aperta - Ziemann, Miriam Helen; Weigand, Markus A. (Surgical endoscopy and other interventional techniques, 2018)
Percutaneous partial amniotic carbon dioxide insufflation (PACI) is one of the most important means for improving visualization during minimally invasive fetoscopic surgery of fetal spina bifida. The purpose of the present study was to analyze maternal and fetal safety aspects of PACI in a recent patient cohort and to present management improvements.
Gesehen am 02.04.2020